Segmentation and efficiency of the interbank market in Kenya - Moses Muse Sichei; Samuel Tiriongo; Chris Shimba (Kenya Bankers Association (KBA), 2012)
This paper studies segmentation and efficiency of the interbank market in Kenya. The study utilizes network framework and case studies of countries with developed interbank markets, namely the UK, EU and the US. Using daily data for the period June 2003 to September 5 2012, the study finds that Kenya's interbank market is incomplete and highly segmented by size: small, medium and large banks. Specifically, large banks tend to discriminate against small banks in terms of credit extended and the interest rate charged, which is usually higher than those charged on their peers. The segmented nature of the market has limited its ability to facilitate banks' liquidity management strategy. The case studies show that the efficiency of the interbank market in Kenya can be enhanced through a number of developments such as adding lending products with maturities of more than one day so us to have a term structure; increasing the number of currencies traded; developing a benchmark interbank interest rate; and increasing linkages with other money market segments and monetary policy.
Keywords: E44; D47; G21; 330; Segmentation; interbank; efficiency; Kenya